2012
DOI: 10.1080/10496505.2012.663694
|View full text |Cite
|
Sign up to set email alerts
|

Information Communication Technology Needs of Small-Scale Farmers in Anambra State, Nigeria

Abstract: This study sought to identify the information communication technology (ICT) needs of small-scale farmers in Anambra State, Nigeria. A structured interview schedule was used to collect data from a sample of 108 farmers. Results revealed that the majority used radio and television and owned mobile phones and video machines. Constraints to use included capacity, infrastructural/technical and logistical problems. The study recommends that the Nigerian government reorient its policies in order to harness the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 4 publications
2
10
0
Order By: Relevance
“…Primary occupation Majority (68.8%) of the respondents had farming as a major occupation, 20% were civil servants, among others (Table 1). This finding agrees with Ajani who observed that most of the people in the rural areas are engaged in subsistence farming [17].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Primary occupation Majority (68.8%) of the respondents had farming as a major occupation, 20% were civil servants, among others (Table 1). This finding agrees with Ajani who observed that most of the people in the rural areas are engaged in subsistence farming [17].…”
Section: Resultssupporting
confidence: 92%
“…They are farmers whose average land holdings is about 1-3 hectares who cannot benefit from economies of scale hence resort to cooperative societies. This buttresses Ajani and Agwu who stated that both the young and aged still produce at the subsistence level in order to feed members of their families [15].…”
Section: Resultsmentioning
confidence: 74%
“…Despite the fact that there is not a common definition of "information needs," the term has been (Bawden, 2006) and remains widely used in many fields-such as agricultural research (Aina, 2012;Ajani & Agwu, 2012;Oladeji, Oyesola, Ogunleye, & Raji, 2011;Villamil, Alexander, Silvis, & Gray, 2012;Yusuf, Masika, & Ighodaro, 2013), health research (Lundgrén-Laine, Kalafati, Kontio, Kauko, & Salanterä, 2013;Reeder, Thompson, & Demiris, 2012;Sullivan, Harlan, Pakenham-Walsh, & Ouma, 2012), food studies (Knopp, 2011;Pham, Jones, Dewey, Sargeant, & Marshall, 2012;Schultz, Nothwehr, Hanson, Chrisman, & Haines, 2012), leisure research (Chen & Qi, 2010;Wong & Liu, 2011), and engineering (Heisig, Caldwell, Grebici, & Clarkson, 2010;Wild, McMahon, Darlington, Liu, & Culley, 2010), to name only a few. In this article the term is used to describe any derivative need, that arises from deficits in a more basic (primary) need-or in a set of simultaneously expressed needs-and which can be satisfied only through the acquisition of information.…”
Section: Information Needsmentioning
confidence: 98%
“…According to Ajani and Agwu (2012), other areas of importance of ICTs indicated by small-scale farmers include: easy access to agricultural information; provision of information on weather, soils, crop, and animal disease outbreaks; provision of information about new farming techniques and new food storage and processing technologies; and quick access to information on market prices of crops and livestock and farm inputs such as fertilizer, agro-chemicals, etc. Other areas of importance include ensuring effective communication with other farmers; availability of information on sources of credit, subsidies, and loans for farming; and ensuring effective communication with extension agencies and NGOs.…”
Section: Introductionmentioning
confidence: 99%